Perception of MIN and MTs Teachers in Jembrana Regency Towards Digital Transformation and Inequality in Access to Education - Edwin, Edwin; Rahmi, Wifqi; Azis, Hendra Sidratul; Sriartha, I Putu (LP. Ma'arif Janggan Magetan, 2024)
This study aims to find out the perception of teachers in MIN and MTs throughout Jembarana Regency related to digital transformation and inequality in access to education in Jembrana Regency. The selection of informant was carried out using a purposive sampling technique with the criteria of having taught for at least two years and being involved in the use of digital technology. Data were collected using semi-structured interview techniques, analysed and presented in a descriptive manner. The results of the study show that teachers see digital transformation as an important step in increasing learning relevance, flexibility, and interactivity. Technology is considered to enrich teaching methods and provide opportunities for students to learn independently through more varied digital media. However, inequality in access to technology, especially in terms of devices and internet connections, is a significant obstacle that hinders the involvement and learning outcomes of students who lack access. Teachers identified the need for policies and infrastructure development that support equal access to digital education as well as sustainable digital literacy training for teachers and students. This finding is expected to be used as a foundation for more responsive and inclusive policy-making to realize equitable digital education.